Real-time fire detection based on feature analysis using enhanced color segmentation and novel foreground extraction - Khan, Rubayat Ahmed (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Science in Computer Science and Engineering, 2017.